"Put the what, where? Cut here?!" challenges to coordinating attention in robot-assisted surgery: a microanalytic pilot study. Issue 7 (14th July 2021) - Satchidanand, Antara; Higginbotham, Jeff; Bisantz, Ann; Aldhaam, Naif; Elsayed, Ahmed; Carr, Iman; Hussein, Ahmed A; Guru, Khurshid
Abstract : Introduction: During robot-assisted surgery (RAS), changes to the operating room configuration pose challenges to communication by limiting team members' ability to see one another or use gesture. Referencing (the act of pointing out an object or area in order to coordinate action around it), may be susceptible to miscommunication due to these constraints. Objectives: Explore the use of microanalysis to describe and evaluate communicative efficiency in RAS through examination of referencing in surgical tasks. Methods: All communications during ten robot-assisted pelvic surgeries (radical cystectomies and prostatectomies) were fully transcribed. Forty-six referencing events were identified within these and subjected to a process of microanalysis. Microanalysis employs detailed transcription of speech and gesture along with their relative timing/sequencing to describe and analyse interactions. A descriptive taxonomy for referencing strategies was developed with categories including references reliant exclusively on speech (anatomic terms/directional language and context dependent words (CD)); references reliant exclusively on gesture or available aspects of the environment (point/show, camera focus/movement in the visual field and functional movement); and references reliant on the integrated use of speech and gesture/environmental support (integrated communication (IC)). Frequency of utilisation and number/percent 'miscommunication', were collated within each category when miscommunication was defined as any reference met with incorrect or no identification of the target. Results: IC and CD were the most frequently used strategies (45% and 26%, respectively, p≤0.01). Miscommunication was encountered in 22% of references. The use of IC resulted in the fewest miscommunications, while CD was associated with the most miscommunications (42%). Microanalysis provided insight into the causes and nature of successful referencing and miscommunication. Conclusions: In RAS, surgeons complete referencing tasks in a variety of ways. IC may provide an effective means of referencing, while other strategies may not be adequately supported by the environment.